Does acupuncture decrease the frequency of tension headaches?. Issue 5 (May 2018) - Cruz, Riza; Wojciechowski, Helena; Sheets, Randall
Abstract : EVIDENCE‐BASED ANSWER : Yes. For tension headaches, acupuncture leads to about a 30% higher overall response rate, slightly more patients achieving a 50% reduction in the frequency of tension headaches, and about 2 fewer headaches days per month compared with sham procedures (SOR: A, meta‐analyses of RCTs).